Indirect Refusal Strategies in Two American and Three British Movies - Curtina Melati Kasih (Lexicon, 2014)
This research focuses on identification and classification of indirect refusal strategies found in two American movies (RV (2006), We’re the Millers (2014)) and three British movies (Chalet Girl (2011), Cuban Fury (2014), and Hot Fuzz (2007)). In particular, it aims to show the different strategy between the refusals of American and British movies. The data were analysed by Félix-Brasdefer taxonomy of indirect refusal strategies (2008, 74-79). The data used in this research were taken through an observation from the subtitle of these five movies. The results of the research show that out of the 92 refusal utterances, 50 were found in the American movies and 42 from the British movies. Based on the findings, the most frequently used strategy from the American movies is Strategy 1: Mitigated Refusal. This strategy was used 11 times (11.96%). In the British movies, the most common strategy is Strategy 2: Reason/Explanation which used 17 times (18.48%). These results suggest that the American and the British have their own ways in delivering refusal. To minimize the negative effects of being refused the American tends to hedge the refusal for making the utterances sounds more polite. Meanwhile, the British tends to explain why they cannot fulfil the interlocutor’s demand.